2005
DOI: 10.2337/diacare.28.10.2400
|View full text |Cite
|
Sign up to set email alerts
|

Dose Response of Inhaled Dry-Powder Insulin and Dose Equivalence to Subcutaneous Insulin Lispro

Abstract: OBJECTIVE -To determine the pharmacokinetic (PK) and glucodynamic (GD) dose response of human insulin inhalation powder (HIIP) delivered via AIR particle technology and dose equivalence to subcutaneous (SC) insulin lispro.RESEARCH DESIGN AND METHODS -Twenty healthy, nonsmoking, male or female subjects (aged 29.6 Ϯ 6.9 years, BMI 23.2 Ϯ 2.3 kg/m 2 , means Ϯ SD) with normal forced vital capacity and forced expiratory volume were enrolled in an open-label, randomized, sevenperiod, euglycemic glucose clamp, cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 24 publications
(29 reference statements)
7
32
0
Order By: Relevance
“…A previous study has shown that the human inhaled insulin powder (HIIP) used in the present study is well tolerated and has a good safety profile [10]. Moreover, HIIP demonstrated a broad range of dose proportionality relative to subcutaneously injected insulin lispro, as well as comparable glucodynamic effects and intra-subject variability.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…A previous study has shown that the human inhaled insulin powder (HIIP) used in the present study is well tolerated and has a good safety profile [10]. Moreover, HIIP demonstrated a broad range of dose proportionality relative to subcutaneously injected insulin lispro, as well as comparable glucodynamic effects and intra-subject variability.…”
Section: Introductionmentioning
confidence: 91%
“…The incidence of severe Data expressed in insulin units, least squares means (SE). No significant differences were observed between the treatments for any of the dosing parameters listed here HIIP doses represent SC unit equivalents that were determined previously in a euglycaemic clamp study conducted in normal volunteers [10] hypoglycaemia was similar for the HIIP and SC insulin treatment periods (12 (Fig. 5b).…”
Section: Hypoglycaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…6 A short DIA hides residual bolus insulin activity, causes unrecognized insulin stacking, and may lead to errors in other settings as the user attempts to compensate for this hidden insulin stacking. One study found that the DIA appeared to depend on the size of the insulin dose, 8 but this apparent dose/time dependency may be an artifact of the glucose infusion rate (GIR) methodology used. In this and Mudaliar's GIR study, the DIA or insulin pharmacodynamics was measured as the time over which glucose infusion was needed to offset an insulin bolus given to healthy individuals.…”
Section: Select An Accurate Duration Of Insulin Actionmentioning
confidence: 99%
“…4 Currently, inhaled insulin is restricted to a shortacting profile and for almost all patients would not completely remove the need for injection. A study by Rave and colleagues 34 compared the timeaction profile of one inhaled insulin, Exubera, with that of a subcutaneously injected insulin analogue, lispro, or regular human soluble insulin in healthy volunteers. Inhaled insulin was found to have a faster onset of action than regular insulin, but was comparable to lispro.…”
Section: Alternative Insulin Treatment Optionsmentioning
confidence: 99%